Manufacturing tracked vehicles at the Kharkov Tractor Plant (mid-twentieth – beginning of the twenty-first century) - Pisarskaya, N. V. (History of science and technology, 2018)
The Kharkov Tractor Plant was and remains the leading center of tractor construction in Ukraine. An important activity of this enterprise was the release of tracked vehicles for both the national economy and military needs. For more than half a century, the plant developed unique tracked vehicles, which were constantly improved thanks to the fruitful activities of the design bureau of the enterprise and individual inventors. This applies not only to civilian tracked vehicles, but also military equipment. It is noted that the creation of tracked vehicles equipment on the territory of Kharkov began before the emergence of the Kharkov tractor plant, but this enterprise played a significant role in the manufacture of this type of machines. During the studied period there was a gradual evolution of samples of tracked vehicles equipment, its continuous improvement made it possible to reach a sufficiently high level of production. In order to improve detailed analysis tracked vehicles process analysis and comparison of different models of machines. This made it possible to reveal how the technical indicators changed and to trace the gradual evolution of this type of machines. In preparing the work, a method of comparative analysis and systematization of available information on the manufacture of tracked vehicles at the Kharkov Tractor Plant was used. The influence of individual designers and inventors on the development and improvement of models of tracked vehicles was also noted. Particular attention is paid to the peculiarities of engines used for both types of tracked vehicles, as well as the continuous improvement of agricultural crop tractors. Analysis of some types of engines it possible to investigate what kind engines were more suitable for use in tracked vehicles. It was specified that in order to separate the design and production of equipment for military purposes from agricultural tractors, two separate design bureaus were created. This has allowed to focus on the features of each type of technology.